DIGNITY AS A MORAL CONCEPT*. Issue 1 (12th February 2014) - Bird, Colin
Abstract: Although dignity figures prominently in modern ethical discourse, and in the writings of moral and political philosophers writing today, we still lack a clear account of how the concept of dignity might be implicated in various forms of moral reasoning. This essay tries to make progress on two fronts. First, it attempts to clarify the possible roles the concept of dignity might play in moral discourse, with particular reference to Hart's distinction between positive and critical morality. Second, it offers a new typology of dignity concepts and mobilizes it to, on the one hand, criticize some familiar construals of "human dignity" and, on the other, to advertise the possible virtues of an unfamiliar way of thinking about dignity as a moral concept.